THE ECONOMIC BURDEN OF CARDIOVASCULAR DISEASES ASSOCIATED WITH UNHEALTHY DIET IN THE RUSSIAN FEDERATION IN 2016. (April 2021) - Mukaneeva, Dinara; Kontsevaya, Anna; Myrzamatova, Azaliia; Balanova, Yulia; Khudyakov, Mikhail; Drapkina, Oxana
Abstract: Objective: To estimate the economic burden of cardiovascular diseases (CVD) attributable to unhealthy diet in the Russian Federation (RF) in 2016. Design and method: According to the ESSE-RF epidemiological study, the prevalence of excess consumption of salt, processed red meat and sugar-sweetened beverages (SSB) in the Russian population was recorded in 49.9%, 22.5 %, 8.6% surveyed, respectively. We first obtained CVD risk estimates for intakes of harmful foods (salt, processed red meat, SSB). The relative risks (RRs) of morbidity and mortality from CVD associated with unhealthy diet were identified through a literature search. Based on the data on the prevalence of excess salt intake, processed red meat and SSB consumption in the Russian population and RRs, the population attributable fractions (PAFs) was calculated for CVD. Associations were presented as RRs and PAFs with 95% CIs. To assess the economic burden, the proportion of the analyzed risk factors in the morbidity and mortality from CVD was determined, and then the proportion in the economic burden of the CVD. The direct costs of the health care system and losses in the economy due to morbidity and mortality from CVD associated with unhealthy diet were determined. The calculations were performed in Microsoft Excel 10.0. (Microsoft, USA). Results: The calculated PAR, associated with excess salt intake, for CVD mortality and morbidity was 5% and 7% respectively; for stroke: in mortality — 17%, in morbidity — 10%. The daily of processed red meat consumption determine 8.6% contribution to the morbidity of coronary heart disease. PAR of SSB consumption for CVD mortality and morbidity – 2%. The economic burden of CVD associated with an unhealthy diet in the Russian Federation in 2016 amounted to 204.2 billion rubles (2.9 billion [Euro sign]). Excessive salt intake makes the largest contribution to this burden. The losses in the economy due to premature mortality (177.2 billion rubles) prevail in the structure of the main burden. Direct medical expenses amounted to 26.9 billion rubles. Conclusions: The significant economic burden associated with preventable disease provides an economic rationale for action to reduce the prevalence of lifestyle-related risk factors.